The Groove Enhancement Machine (GEM): A Multi-Person Adaptive Metronome to Manipulate Sensorimotor Synchronization and Subjective Enjoyment - Fink, Lauren K.; Alexander, Prescott C.; Janata, Petr (Frontiers in Human Neuroscience, 2022)
Synchronization of movement enhances cooperation and trust between people. Typically, however, the degree to which individuals can synchronize with each other depends on their ability to perceive the timing of others’ actions and produce movements accordingly. Here, we introduce an assistive device – a multi-person adaptive metronome – that can be used to facilitate synchronization abilities. The adaptive metronome is implemented on Arduino Uno circuit boards, allowing for negligible temporal latency between tapper input and adaptive sonic output. Across five experiments - two single-tapper, and three group (four tapper) experiments - we analyzed the effects of metronome adaptivity and auditory feedback on tapping performance and subjective ratings. In all experiments, tapper synchronization with the metronome was significantly enhanced with 25-50% adaptivity, compared to no adaptation. In group experiments with auditory feedback, synchrony remained enhanced even at 70-100% adaptivity; however, without feedback, synchrony at these high adaptivity levels returned to near baseline. Subjective ratings of being in the groove, in synchrony with the metronome, in synchrony with others, liking the task, and difficulty could all be reduced to one latent factor, which we termed enjoyment. This same factor structure replicated across all experiments. In predicting enjoyment, we found an interaction between auditory feedback and metronome adaptivity, with increased enjoyment at optimal levels of adaptivity only with auditory feedback and a severe decrease in enjoyment at higher levels of adaptivity, especially without feedback. Exploratory analyses relating person-level variables to tapping performance showed that musical sophistication and trait sadness contributed to the degree to which an individual differed in tapping stability from the group. Nonetheless, individuals and groups benefitted from adaptivity, regardless of their musical sophistication. Further, individuals who tapped less variably than the group (which only occurred 25% of the time) were more likely to feel “in the groove.” Overall, this work replicates previous single person adaptive metronome studies and extends them to group contexts, thereby contributing to our understanding of the temporal, auditory, psychological, and personal factors underlying interpersonal synchrony and subjective enjoyment during sensorimotor interaction. Further, it provides an open-source tool for studying such factors in a controlled way.